Orbital Angular Momentum for Wireless Communications: Key Performance Indicators and Performance Comparison - Zihao Wang; Mohammed El-Hajjar; Lie-Liang Yang (IEEE Access)
Orbital angular momentum (OAM) is an intrinsic property of electromagnetic (EM) waves that has opened new possibilities for enhancing the capacity of wireless communications. Consequently, it has garnered significant attention in recent years. For wireless communications, antenna arrays are the most effective and widely studied approaches for OAM-wave generation. Various types of antenna arrays have been explored in research and development; however, a comprehensive comparison of these arrays remains lacking. This paper addresses this gap by first reviewing the various types of phased arrays that have been considered for OAM generation in the literature. Subsequently, it addresses the key performance indicators (KPIs) of the antenna arrays for OAM-wave generation. These KPIs include directivity, the largest producible OAM-mode (LPM), OAM-mode multiplexing capability, divergence angle, and mode purity. Based on the KPIs, a comparative analysis is conducted across several types of antenna arrays, including uniform square arrays (USA), uniform circular arrays (UCA), three-dimensional (3D) helical circular arrays (HCA), 3D helical circular sub-arrays (HCSA), and concentric UCAs (CUCA), under various settings. The study highlights the advantages and limitations of each antenna array type and examines how different parameters influence their performance.